2010
DOI: 10.1245/s10434-010-0921-7
|View full text |Cite
|
Sign up to set email alerts
|

CpG Island Methylator Phenotype Associated with Tumor Recurrence in Tumor–Node–Metastasis Stage I Hepatocellular Carcinoma

Abstract: CIMP+ may specifically define a subgroup of patients with unfavorable outcome in TNM stage I HCC. Examination of CIMP status may be useful for stratifying prognosis of patients with early-stage HCC and identifying patients who are at higher risk for recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…In the meantime, the present study confirmed that the methylation frequency of ELF, RASSF1A, p16, and GSTP1, the average number of methylated genes or methylation frequencies with combination of at least two or three genes in HCC tissues were significantly higher than in nontumor, which is in consistence with previous reports (Lee et al, 2003;Yang et al, 2003;Wang et al, 2006;Li et al, 2010). All these results suggest that events of DNA methylation had taken place even early in the liver injury stages, and a trend of increase of methylated genes occurred during progression of HCC.…”
Section: Discussionsupporting
confidence: 92%
“…In the meantime, the present study confirmed that the methylation frequency of ELF, RASSF1A, p16, and GSTP1, the average number of methylated genes or methylation frequencies with combination of at least two or three genes in HCC tissues were significantly higher than in nontumor, which is in consistence with previous reports (Lee et al, 2003;Yang et al, 2003;Wang et al, 2006;Li et al, 2010). All these results suggest that events of DNA methylation had taken place even early in the liver injury stages, and a trend of increase of methylated genes occurred during progression of HCC.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our results, one previous study showed that HCC features a high frequency of CpG island hyper-methylation in the promoter regions; the aberrant hyper-methylation of GSTP1 tends to accelerate during the multistep process of hepatocarcinogenesis, and might be a possible means of predicting the development of HCC, especially in the premalignant stages (Lee et al, 2003). Similarly, Li et al (2010) concluded that CpG island methylation of GSTP1 may specifically define a subgroup of patients with unfavorable outcomes in TNM stage I HCC, suggesting that the examination of GSTP1 methylation may be useful for stratifying prognosis of patients with early-stage HCC and identifying patients who are at higher risk of recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…According to the inclusion criteria, 14 cohort studies were included (Zhong et al, 2002;Lee et al, 2003;Tada et al, 2005;Wang et al, 2006;Zhang et al, 2006;Su et al, 2007;Harder et al, 2008;Chang et al, 2008;Moribe et al, 2009;Kiran et al, 2009;Li et al, 2010;Feng et al, 2010;Hua et al, 2011;Jain et al, 2012) and 89 articles were excluded. A total of 607 HCC samples in 14 cohort studies were included; additionally, 356 adjacent samples, 182 benign samples, and 133 normal samples were included.…”
Section: Baseline Characteristics Of Studies Includedmentioning
confidence: 99%
“…Promoter methylation of p15 and p16 resulting in unopposed cyclin D-CDK6 activation is a molecular mechanism conferring adverse prognosis in HCC. 82 A confirmation of the detrimental effect of p16 and p18 loss on patient prognosis comes from studies analyzing their immunohistochemical expression. 83,84 On the contrary, p16 gene sequence alterations do not seem to influence survival 85 and in an earlier study, methylation-specific PCR analysis of p16 inactivation did not correlate with prognosis.…”
Section: Cyclins Cyclin-dependent Kinases and Its Regulatorsmentioning
confidence: 99%